PRIMA SERVICE EFFECTIVENESS PT. BANK ACEH SHARIAH TO CUSTOMER LOYALTY - M. Yazid AR (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study entitled "Effectiveness of Excellent Service PT. Bank Aceh Syariah Against Customer Loyalty”. This study aims to determine the effectiveness of the best service for loyal customers of PT Bank Aceh Syariah who take samples at the Lhokseumawe branch. The population of this study were all customers of PT Bank Aceh Syariah Lhokseumawe branch. The research method used is quantitative. A sample of 100 respondents was obtained using a random sampling technique. For data collection, primary data was obtained through interviews, questionnaires and direct observation. In this study, analytical methods were used to analyze the data. Data processing was carried out using SPSS Statistics version 20. From the partial research results, the variables that did not help and were helpful were ability, similarity, and responsibility. Variables that have a positive and significant effect are attitudes, preferences and behavior. Simultaneous testing shows that all changes are effective and affect customer loyalty of PT Bank Aceh Syariah Lhokseumawe branch.